Brain Metastasis of Nasopharyngeal Carcinoma: A Case Report and Literature Review - Orit Kaidar-Person; Jonathan Kuten; Fadi Atrash; Salem Billan; Abraham Kuten (Case Reports in Medicine)
Central nervous system metastases from nasopharyngeal carcinoma (NPC) are uncommon. The patient presented was diagnosed with aggressive advanced NPC resistant to treatment and complicated by a solitary brain metastasis. A PubMed database search was conducted to review the existing literature regarding brain metastases of NPC, using the search terms “nasopharyngeal neoplasia,” “nasopharyngeal carcinoma,” “nasopharynx,” “radiotherapy,” “central nervous system,” and “brain” in section of “Title/Abstract.” The articles were first evaluated by title and then by abstract, and thereafter appropriate manuscripts were evaluated by full text. References of the published papers were also reviewed.